Requirements of Application and Sphere of Applicability of the CISG - Schlechtriem, Peter (Victoria University of Wellington Law Review, 2005)
Professor Schlechtriem begins by suggesting the success of the Convention on the International Sale of Goods can be explained by its simplicity. In this paper, however, he goes on to explain and expand on some of the complexities of interpretation of the Convention, especially those in part one caused by difficulties created by reservations. However, his paper ends by suggesting that, despite the complexities, the CSIG often remains far preferable to the use of national law that may itself be uncertain or even unknown.